Trajectory Detection Method for Transmission Line Path Following Control - Pusssente, Guilherme Augusto Namorato; Maria, Tiago Henrique Santa; Marcato, André Luís Marques; Aguiar, Eduardo Pestana de (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
The use of robots for inspection of transmission lines has been the target of several studies nowadays, allowing the replacement of manual supervision. The goal of this paper is to present a strategy for the estimation of a trajectory for the tracking of UAVs on these power lines based on the Hough Transform with the iterative RANSAC method. The purpose of this calculation is to define the parameters that will be inserted into the NMPC Control that will determine the required control actions to solve the visual path tracking problem. Practical tests show that the proposed method was effective with the UAV maintaining the trajectory with low errors.